In situ XRD analysis of dolomite calcination under CO2 in a humid environment. Issue 39 (7th September 2020) - Medina-Carrasco, Santiago; Valverde, Jose Manuel
Abstract : In situ XRD analysis on the calcination and decrepitation of natural dolomite under pure CO2 atmosphere and influence of humidity under conditions relevant for CO2 capture. Abstract : The present work reports an in situ XRD analysis on the calcination of natural dolomite under a pure CO2 atmosphere. The main goal is to provide an insight on how calcination kinetics and the crystal structure of the calcination byproducts are affected by the addition of H2 O to the calciner at a very low concentration. The working conditions are relevant for CO2 capture from fossil fuel power plants and thermochemical energy storage (TCES) in concentrated solar power (CSP) plants. It is shown that the presence of H2 O in the calciner at the low concentration used in our study (3 vol%) yields a significant acceleration of dolomite decomposition whereas crystallite size of the reaction byproducts is not affected if fine particles are used. On the other hand, decrepitation, which is a well know phenomenon that occurs when relatively large particles are employed, is accompanied by a marked decrease of crystallite size.